(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
ies widely known as pests only Parthenolecanium comi (Bouché), P. pomeranicum (Kawecki), Aulacaspis rosae (Bouché ), Carulaspis juniperi (Bouché ), Lepidosaphes ulmi (L.) and Leucaspis pini (Hartig) are of great economie importance as they appeared with high frequency and high density, in the Kazimierz Landscape Park. The species which are characterized by low frequency, but appearing on their hosts with high density are also of economie significance for trees and shrubs. These are: Kermes quercus (L.), Parthenolecanium rufulum (Cockerell), Asterodiaspis variolosa (Ratzeburg), Chionaspis salicis (L.) and Leucaspis loewi (Colvée). Attention should also be paid to Planococcus vovae (Nassonov) which was characterized by relatively high frequency, but occurred on the junipers only at low density. Another group of scale insects was composed of the species which were characterized by low frequency and occurred on their hosts only at low density.